PENGEMBANGAN BAHAN AJAR MATEMATIKA EKONOMI BERBASIS LEARNING CYCLE BERBANTUAN SOFTWARE GEOGEBRA UNTUK MENINGKATKAN HASIL BELAJAR MAHASISWA - Sumarni Sumarni; Anggar Titis Prayitno; Mita Nurpalah3 (Jurnal Edukasi dan Sains Matematika (JES-MAT), 2017)
AbstractThis article examines the development of economic  mathematics learning materials based on learning cycle assisted by GeoGebra software to improve student learning outcomes. The purpose of this study: 1) Obtaining the economic mathematics teaching materials developed in according with the principle of model learning cycle 5E; 2) Obtaining the developed economic mathematics material meets the valid and practical criteria; 3) Obtaining the mathematical materials of the developed mathematics economy can improve student learning outcomes. Stages or procedure research development that is requirement analysis; product development (teaching materials); expert validation and product revision; small-scale field trials. The results obtained in this study: 1) have developed economic mathematics learning materials based on learning cycle assisted GeoGebra software 2) Based on the validator's assessment, economic mathematics based on based learning cycle assisted GeoGebra software in good category with percentage of idealization of 77.96%. 3) Based on field trials, teaching materials that are developed the economic mathematics learning materials based on learning cycle assisted GeoGebra software can improve student learning outcomes. Improved student learning outcomes using economic mathematics learning materials based on learning cycle assisted GeoGebra software is better than students who do not use economic mathematics learning materials based on learning cycle assisted GeoGebra software. Keywords : Learning Outcomes, Learning Cycle, Economic Mathematics, Development of Teaching Materials, GeoGebra Software